Lawyers in Libraries: A New Approach to Justice in Maine - Mead, Andrew (Maine Policy Review, 2013)
Andrew Mead describes the emerging partnership between libraries and lawyers, whereby lawyers provide pro bono legal advice in libraries both in person and through remote teleconferencing capability.